BOYCOTTS AND THE SOCIAL ENFORCEMENT OF JUSTICE. Issue 1 (14th June 2017) - Radzik, Linda
Abstract: This essay examines the ethics of boycotting as a social response to injustice or wrongdoing. The boycotts in question are collective actions in which private citizens withdraw from or avoid consumer or cultural interaction with parties perceived to be responsible for some transgression. Whether a particular boycott is justified depends, not only on the reasonableness of the underlying moral critique, but also on what the boycotters are doing in boycotting. The essay considers four possible interpretations of the kind of act in which boycotting consists: the avoidance of complicity, protest speech, social punishment, or social coercion. Each interpretation provides a plausible account of at least some cases of boycotting, yet each raises distinct challenges to justifying boycotting activities.